2020
DOI: 10.1101/2020.01.24.916015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid and scalable profiling of nascent RNA with fastGRO

Abstract: Genome-wide profiling of nascent RNA has become a fundamental tool to study transcription regulation. Over the past decade, next-generation sequencing has fostered development of a handful of techniques (i.e. GRO-seq, PRO-seq, TT-seq and NET-seq) that map unprocessed transcripts originating from both the coding and the noncoding portion of the genome. Unlike steady-state RNA sequencing, nascent RNA profiling mirrors the real-time activity of RNA Polymerases and provides an accurate readout of transcriptome-wid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…To determine the effect of INTS6/PP2A loss on acutely activated genes that were suppressed by CDK9i, INTS6 was depleted in HeLa cells ( Figure S5J) and cells were pre-treated with AZ5576 for two hours prior to stimulation with EGF for 15 minutes. ChIP-seq assays demonstrated that total RNAPII and RNAPII phospho-Ser2 accumulated genome-wide in INTS6-depleted HeLa cells treated with AZ5576, with accumulation most clearly observed across the gene bodies of EGF-responsive genes, in contrast to the reduced ChIP-seq signal observed in control shLUC cells ( Figure 5H Consistent with the ChIP-seq data for RNAPII and RNAPII phospho-Ser2 detailed above, fastGRO assays (Barbieri et al, 2020) to assess nascent RNA production demonstrated that depletion of INTS6 in HeLa cells counteracted CDK9i-induced transcriptional pausing at all EGF-stimulated genes ( Figure 5J-K). A broader analysis of the highest-expressed genes (n=2989) demonstrated that INTS6 depletion decreased the pausing index of nearly all active genes ( Figure 5L), similar to the effects observed in THP-1 sgINTS6-KO cells treated with AZ5576 ( Fig 5F).…”
Section: Loss Of Ints6/pp2a Overrides a Cdk9i-dependent Block Of Transupporting
confidence: 83%
See 1 more Smart Citation
“…To determine the effect of INTS6/PP2A loss on acutely activated genes that were suppressed by CDK9i, INTS6 was depleted in HeLa cells ( Figure S5J) and cells were pre-treated with AZ5576 for two hours prior to stimulation with EGF for 15 minutes. ChIP-seq assays demonstrated that total RNAPII and RNAPII phospho-Ser2 accumulated genome-wide in INTS6-depleted HeLa cells treated with AZ5576, with accumulation most clearly observed across the gene bodies of EGF-responsive genes, in contrast to the reduced ChIP-seq signal observed in control shLUC cells ( Figure 5H Consistent with the ChIP-seq data for RNAPII and RNAPII phospho-Ser2 detailed above, fastGRO assays (Barbieri et al, 2020) to assess nascent RNA production demonstrated that depletion of INTS6 in HeLa cells counteracted CDK9i-induced transcriptional pausing at all EGF-stimulated genes ( Figure 5J-K). A broader analysis of the highest-expressed genes (n=2989) demonstrated that INTS6 depletion decreased the pausing index of nearly all active genes ( Figure 5L), similar to the effects observed in THP-1 sgINTS6-KO cells treated with AZ5576 ( Fig 5F).…”
Section: Loss Of Ints6/pp2a Overrides a Cdk9i-dependent Block Of Transupporting
confidence: 83%
“…FastGRO was performed as described (Barbieri et al, 2020). HeLa cells infected with shLUC or shINTS6 were treated with DMSO or 300nM CDK9i AZ5576 for 2 hours, then subsequently treated for 15 minutes with 0.1μg/mL EGF.…”
Section: Fastgromentioning
confidence: 99%
“…In agreement with a role for INTS8 in PP2A recruitment, its depletion phenocopied INTS6 loss and conferred resistance to CDK9i-induced pausing (Figures S5O-S5Q). FastGRO assays (Barbieri et al, 2020) measuring nascent RNA production also showed that INTS6 depletion counteracted CDK9i-induced transcriptional pausing at all EGF-stimulated genes, whereas a broader analysis of the most highly expressed genes demonstrated that INTS6 depletion decreased the pausing index at these active loci (Figures 5J-5L). To determine whether PP2A depletion can also drive escape from CDK9i-induced pausing, analogous assays were also performed in HeLa cells with shRNA-mediated knockdown of PPP2R1A (Figure S5R).…”
Section: Loss Of Ints6/pp2a Overrides a Cdk9i-induced Block In Transc...mentioning
confidence: 94%
“…FastGRO was performed as described (Barbieri et al, 2020). HeLa cells infected with shLUC or shINTS6 were treated, 72 hours after infection, with DMSO or 300nM CDK9i AZ5576 for 2 hours, then subsequently treated for 15 minutes with 0.1 mg/mL EGF.…”
Section: Fastgromentioning
confidence: 99%
“…To capture all RNAs arising from cellular RNA polymerases, several run-on transcription capture protocols, such as global run-on sequencing (GRO-seq) and precision run-on sequencing (PRO-seq), have been developed [1,8,3,9,10]. These protocols, collectively known as RO-seq, follow roughly a two step process: first, the run-on RNA signal must be enriched above the background total RNA; second, the captured RNA must then be converted into a sequencing-ready cDNA library [1].…”
Section: Introductionmentioning
confidence: 99%